English Language Teachers’ Perception of Teaching Writing in Nepali High Schools - Pandey, Madhukar (Journal of TESON, 2022)
Writing is a part of learning a language in any academic institution. As teaching writing is a process of learning this article tries to dig out the reasons why teaching writing is becoming complex and rigid in Nepali high school classrooms. In this study, for the purpose of data collection, ten Nepali high school English teachers were interviewed and they shared their experiences of teaching writing skills in their classrooms. The study found some issues that make teaching writing more complex: central- design curriculum, a lack of resources and training, and a lack of English competency of the students in the classrooms. Moreover, students’ performance in grammar, word combination, and sentence composition is rather low that does not encourage students to write. Hence, teaching writing in Nepali high school classrooms is considered a complex genre.